In vitro morphogenic responses of vasconcellea chilensis planch. ex a. dc (caricaceae) (2011)
Multiple shoot formation was induced in vitro on nodal sections excised from adult “palo gordo” plants of Vasconcellea chilensis ex Carica chilensis, in the presence of relatively high levels of thidiazuron (TDZ), indole-3- acetic acid (IAA) and organic addenda included in the WPM formulation including casein hydrolysate, adenine sulfate and cystein. Multiple shoots appeared simultaneously in strands or clusters on the surface of the explants; usually two or more clusters with new shoots were initiated, all showing synchronous growth. In subculture, in the presence of indole-3-butyric acid (IBA) as single hormone, root formation did not take place; the shoots turned green instead, evidenced elongation and development of new shoots at the base of the explants. Other explants, such as petioles and leaf sections exhibited callus initiation upon the vascular system after 4-5 weeks; however, this tissue turned brown later on and died.